(untitled) (World Science, 2019)
Experience of studying and generalization of materials of research, modeling, normalization and approbation of experimental designing of a number of cities-centers of agglomerations of Ukraine, allowed to develop recommendations for a method of designing of long-term formation and sustainable development. These recommendations include solving the problems of formation and development of the structure of these cities, the step-by-step nature of their decision, the targeted, resource-normative approach of functional planning and forecasting, as well as the methodical scheme of operational organization of the design and implementation process. Setting and solving problems of long-term structure formation and sustainable development of urban complex zones, districts and districts of settlements of urban centers of agglomerations is based on the analysis of urban processes and formation of structure and infrastructure of these multifunctional entities. In solving development problems, the dynamics of changes in the structure and infrastructure of urban complex settlements are analyzed, taking into account agglomeration and regional processes and periodization of sustainable development. The proposed method of consistent and gradual choice of rational direction of sustainable development of metropolitan centers of agglomerations is based on the gradual transition from perspectives of development and long-term forecasting to problems of medium and short-term planning and design. The main purpose of this methodology is to focus on the maximum effect of urban planning, taking into account the long-term sustainable perspective with the disclosure of the mechanisms of its formation and development by finding optimal proposals between the processes of autonomization and integration of the city centers of agglomerations and zones of their impact (agglomeration, region) at each stage long-term sustainable development, taking into account development reserves.